2013
DOI: 10.3109/14764172.2012.748201
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Skin rejuvenation by microneedle fractional radiofrequency and a human stem cell conditioned medium in Asian skin: a randomized controlled investigator blinded split-face study

Abstract: Microneedle fractional RF is a safe and effective skin rejuvenation method, and the better results may be expected when combined with stem cell conditioned medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 14 publications
3
60
1
1
Order By: Relevance
“…A novel method of combining microneedle fractional radiofrequency and conditioned medium in skin aging demonstrated clinical benefit and increase in dermal collagen content [30]. Subsequently, Lee et al reported benefit of delivering growth factors through 0.25 mm microneedle for skin rejuvenation in a randomized, blinded study [31].…”
Section: Discussionmentioning
confidence: 99%
“…A novel method of combining microneedle fractional radiofrequency and conditioned medium in skin aging demonstrated clinical benefit and increase in dermal collagen content [30]. Subsequently, Lee et al reported benefit of delivering growth factors through 0.25 mm microneedle for skin rejuvenation in a randomized, blinded study [31].…”
Section: Discussionmentioning
confidence: 99%
“…Se acompañan de un dispositivo con un cilindro rodante, o roller, que se desliza sobre la superficie cutánea. También existen sistemas que emiten la radiofrecuencia fraccionada a través de un sistema de agujas que permite introducir la energía en planos tisulares más profundos [66][67][68][69][70] .…”
Section: Radiofrecuenciaunclassified
“…All patients showed clinical improvement on wrinkle, skin laxity and skin texture and side effects were minimal and well tolerable. 21 Consensus panel members agreed that FRM system will not replace standard surgical treatment such as rhytidectomy. However, FRM system may play a major role in the cosmetic improvement of early skin laxity and be preferred by patients who wish to avoid surgery for the fear of its associated risk of complications.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…5,20 Furthermore, skin needling with microneedles has been reported to stimulate migration and proliferation of keratinocytes and fibroblasts by inducing the release of several growth factors. 5,20,21 And, untreated areas which are located between treated areas serve as a reservoir of cells that promote and accelerate wound healing. 20,21 Histologic and ultra-structural changes Lim et al histologically evaluated pig skin up to 10 weeks after FRM treatment, using energies from 1.25 to 6.25 J/cm 2 .…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation